Expert opinion and key recommendations for the physical therapy and rehabilitation of patients with ankylosing spondylitis - Ozgocmen, Salih; Akgul, Ozgur; Altay, Zuhal; Altindag, Ozlem; Baysal, Ozlem; Calis, Mustafa; Ugur, Mahir (Wiley, 2012)
Aim: Physiotherapy is an integral part of the management of ankylosing spondylitis (AS) and there is a need for recommendations which focus on the rehabilitation of patients with AS. We aimed to develop recommendations for the physical therapy and rehabilitation of patients with AS based on the evidence and expertise. Methods: The Anatolian Group for the Assessment in Rheumatic Diseases (ANGARD) is a scientific group of Turkish academicians (physiatrists and rheumatologists) who are experts in the rehabilitation of patients with AS. A systematic literature search summarizing the current available physiotherapy and rehabilitation trials in AS were presented to the experts before a special 2-day meeting. Experts attending this meeting first defined a framework based on the main principles and thereafter collectively constructed six major recommendations on physiotherapy and rehabilitation in AS. After the meeting an email survey was conducted to rate the strength of the recommendations. Results: Six key recommendations which cover the general principles of rehabilitation in AS in terms of early intervention, initial and follow-up assessments and monitoring, contraindications and precautions, key advice for physiotherapy methods and exercise were constructed. Conclusion: These recommendations were developed using evidence-based data and expert opinion. The implementation of these recommendations should encourage a more comprehensive and methodical approach in the rehabilitation of patients with AS. Regular lifelong exercise is the mainstay of rehabilitation and there is a considerable need for well-designed studies which will enlighten the role of physical therapy in the management of AS.
Keywords: ankylosing spondylitis; physiotherapy; recommendations; rehabilitation